Effect of chain length and fluorination on the dielectric and electro-optic properties of three partially fluorinated biphenylyl benzoate rigid core based ferroelectric liquid crystals. Issue 11 (1st September 2016) - Goswami, Debarghya; Debnath, Asim; Mandal, Pradip Kumar; Wegłowska, Dorota; Dabrowski, Roman; Czupryński, Krzysztof
ABSTRACT: Three partially fluorinated ferroelectric liquid crystals (4F4R, 4F5R and 7F3R) with biphenylyl benzoate rigid core have been investigated by frequency-dependent dielectric spectroscopy and electro-optic methods. Molecular structures of the compounds differ only by the length of the carbon chain and the number of oligomethylene spacers. 4F4R and 4F5R exhibit ferroelectric SmC* phase over a considerable temperature range and directly melts into isotropic phase, 4F4R also shows a ferroelectric type subphase . Only Goldstone mode (GM) relaxation is observed in these compounds, but no soft mode (SM). 7F3R exhibits both the SmC* and SmA* phases, has higher stability of SmC*. Both the GM and SM relaxations are observed in this case, signifying that SM relaxation is possible only when SmC* is formed on cooling from SmA*. Increase of dielectric strength and critical frequency with temperature, in all cases, has been explained in the light of generalised Landau model. Spontaneous polarisation is found to decrease with increasing flexibility, and optical tilt depends more on fluorination than on chain length. GRAPHICAL ABSTRACT: